(3GdLhGgQ GdUajI ef GdeMGSf GdjhSajIs - (3GdaGSj , eMeO Hf CMeO Hf Ydj Hf jhSa, CHh YHO Gddg,J (B1109 (3g` s ((3eMeO Hf bGSe Hf YHOGdSdGe GdHGOSj s)
(3ChdgG (B:s
(3GdMeO ddg Gdhdj GdMejO GdPi NU ef TGA He TGA ef GdYHjO s
(3BNQgG (B:s
(3hUdj Gddg Ydi SjOfG hehdGfG eMeO bWH OGFQI GdceGd ced HMeO Gddg hMSf Yhfg GdLejd hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B119 (3C (B- (3U(B126 (3Cs
(3YQa ajg LOg GdTjN CHj GdeMGSf jhSa Hf eMeO aJMG GdaGSj GdagQj GdeJhaj (B1013(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B301s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B145 s
Keywords: (3GdJGQjNs